2014
DOI: 10.1186/1756-8722-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing aptamer probes for acute myelogenous leukemia detection and surface protein biomarker discovery

Abstract: BackgroundThe majority of patients with acute myelogenous leukemia (AML) still die of their disease. In order to improve survival rates in AML patients, new strategies are necessary to discover biomarkers for the detection and targeted therapy of AML. One of the advantages of the aptamer-based technology is the unique cell-based selection process, which allows us to efficiently select for cell-specific aptamers without knowing which target molecules are present on the cell surface.MethodsThe NB4 AML cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…In fish, with purified virus particles used as targets, RNA aptamers with therapeutic potential were generated against viral hemorrhagic septicemia virus and Hirame rhabdovirus (Hwang et al, 2012;Punnarak et al, 2012). In a previous study, we selected a panel of DNA aptamers against purified SGIV particles, and demonstrated their inhibitory effects on viral infection in vitro and in vivo (Li et al, 2014 Verdaguer et al, 2014). Based on these modifications, or other markers of virus-infected cells, highly specific molecular probes could be designed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fish, with purified virus particles used as targets, RNA aptamers with therapeutic potential were generated against viral hemorrhagic septicemia virus and Hirame rhabdovirus (Hwang et al, 2012;Punnarak et al, 2012). In a previous study, we selected a panel of DNA aptamers against purified SGIV particles, and demonstrated their inhibitory effects on viral infection in vitro and in vivo (Li et al, 2014 Verdaguer et al, 2014). Based on these modifications, or other markers of virus-infected cells, highly specific molecular probes could be designed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of known SGIV target molecules in cell membranes is low, thereby limiting the development of biomarker probes via traditional antibody-based techniques. Aptamers have been used to recognize targets on and within cell membranes via Cell-SELEX technology (Shangguan et al, 2008a, b;Simaeys et al, 2014;Yang et al, 2014). Shangguan et al (2008a) applied Cell-SELEX technology to leukaemia research and found that protein tyrosine kinase 7 was highly expressed in a series of leukaemia cell lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aptamers have been developed for flow cytometric identification of various tumor cells, such as small cell lung cancer, breast and gastric cancers, acute myelogenous leukemia and glioblastoma among further examples (21,26,(47)(48)(49)(50)(51).…”
Section: Flow and Image Cytometry And Aptamersmentioning
confidence: 99%
“…Thus, the identification of target protein(s) for aptamers is a challenging task. Through extraction and affinity purification of proteins of cancer cells with the use of cellrecognition aptamers, protein tyrosine kinase 7 and Siglec-5 were identified as protein targets for aptamers that can bind to T-lineage acute lymphoblastic leukemia cells (8) and acute myelogenous leukemia cells (9), respectively. In addition, an aptamer-facilitated biomarker discovery method was developed for the identification of biomarkers of immature and mature dendritic cells (10).…”
mentioning
confidence: 99%